The impact of Kurdish electronic journalism on providing university students with political information: A study in light of social responsibility theory – a field study - صالح, پاڤێ جميل احمد (Sulaimani Journal for Humanities, 2019)
Nowadays, the electronic newspapers are one of the vital and significant media among other mass media mediums such as newspaper, radio, and TV due to its capacity to combine text, audio, and video together as multimedia. The electronic newspaper also has an aptitude to put an audience in the heart of incidents through the live stream which will make the message and contents more reliable. This research explores the impact of Kurdish electronic newspapers to provide university student with political information. The social responsibility theory has been used in order to comprehend of how the electronic media played its role to make public opinion among university students as well as to recognize that whether the messages passing through electronic newspapers delivered to audiences particularly students who use this medium to get the information or not. The researcher is analytical descriptive that the researcher outline the questionnaire which was distributed to 150 participants, different ages, sex, at universities in the Kurdistan region.